Dengue cases imported from Cuba to Spain, 2022 (Boletín Epidemiológico Semanal, 2024)
Introduction: Dengue is a disease mainly imported into Spain from endemic areas. The objective was to analyse the frequency and characteristics of dengue imported cases from Cuba to Spain in 2022.Method: Descriptive analysis of imported cases from 2016 to 2022, by place of infection (Cuba vs. other).Results: In 2022 there was a predominance in the proportion of cases from Cuba (66.5%) compared to previous years. Among cases, 177 (53.5%) were women with median age of 37 years. 52.0% travelled for tourism and the proportion of hospitalizations was similar between those from Cuba and others.Discussion: The high proportion of cases from Cuba to Spain in 2022 correlated with a dengue alert in Cuba and a higher number of imported cases in other territories. To know the epidemiological situation in endemic places and the country of infection can contribute to the prevention of imported cases in non-endemic territories.
Keywords: dengue; surveillance; Spain; imported cases